Representations of anti-racism in contemporary formation - Manal Rayhan Salman; Ali Sherif Jabr (Basrah Arts Journal, 2023)
Racism is barbaric practices based on prejudice and intolerant behaviors and is based on the persecution and marginalization of individuals or groups for reasons such as differences in religion, color, race, language or culture. It consists of four chapters. The first chapter is devoted to the causes and problem of the research, represented by the following question: How was the anti-racism represented in contemporary formation? The research also aims to identify the representations of the object of anti-racism in the contemporary formation, while the objective boundaries represented in the artworks of artists that carried representations of racism were identified, and the temporal boundaries included the works of art completed in the period (1818-2020). As for the second chapter, which is represented by the theoretical framework and previous studies And it included three topics, where the first topic was devoted (a reading in the concept of racism and its rejection), and what came in the second topic is anti-racism in the history of contemporary formation, while the third chapter concerned the research procedures, and the researcher included the research community in the light of which the research sample was selected, as well In the research tool, the researcher relied on the results of the indicators in the theoretical framework, which is considered the basis of the analysis, in addition to the observation tool, which is one of the tools of the descriptive approach. The fourth chapter included the results, conclusions, recommendations, and proposals.